Travels and Sustainable Tourism in Italy. Selected Dilemmas - MROZEK, Michał (Journal of Environmental Management and Tourism; Vol 14 No 5 (2023): JEMT, Volume XIV, Issue 5(69), Fall 2023DO - 10.14505/jemt.v14.5(69).21, 2023)
The scientific article regards travels and sustainable tourism in Italy in terms of employment, spending, and GDP. The principal purpose of the article is the analysis of travels and sustainable tourism in Italy in terms of employment, spending, and GDP. The paper carried out the documentation analysis, but also very important was the application of the statistical, dynamics, and comparative analysis. The time scope of the study is 2019-2021. Italy's economic recovery will be greatly aided by the travels and sustainable tourism, according to the World Travel and Tourism Council (WTTC). In 2020, the sector was just 0.3% below its pre-pandemic levels. The sector's contribution to GDP in 2019 exceeded €194 billion, according to the World Trade and Technology Council's (WTTC) latest Economic Impact Report (EIR). However, employment in the industry may return to levels seen before the epidemic. Further, the Travel & Tourism industry in Italy is expected to increase at an average annual rate of 2.5 percent over the next ten years, which is five times the growth rate of 0.5 percent of the country's entire economy. In the meanwhile, it's expected to surpass €226 billion by 2032.